A CONTENT ANALYSIS OF “ENGLISH FOR NUSANTARA” FOR SEVENTH JUNIOR HIGH SCHOOL - Hidayah, Vita Tri Kurniawati; Zahro, Syifa’ Khuriyatuz (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
Textbooks are essential in the teaching and learning process, offering structured guidance to achieve the goals of language learners. This study aimed to evaluate the English textbook "English for Nusantara" for the seventh grade year students of Junior High School, published by the Ministry of Education, Culture, Research, and Technology, within the context of Indonesia’s Merdeka Curriculum. Using a qualitative descriptive research design, the content of the textbook was analyzed based on BSNP (Badan Standar Nasional Pendidikan) criteria to assess its relevance and suitability for young learners. Findings reveal that the textbook meets most BSNP standards, making it a suitable resource for teaching English at the junior high school level. However, several areas could benefit from further enhancement, particularly in content depth and cultural representation, to better support language acquisition and engagement. This study highlights the importance of continuous content evaluation to align educational materials with evolving curriculum standards.